The relationship between multiple intelligence profiles and reading strategy use of successful English as a Foreign Language (EFL) readers - Iyitoglu, Orhan; Aydin, Hasan (EDUCATION ASSOC SOUTH AFRICA, 2015)
This study relied on Sheorey and Mokhtari's (2001) metacognitive knowledge about reading strategies, which was influenced by a number of factors, including previous experiences, beliefs, culture-specific instructional practices and proficiency in a second language (L2). This study is thereby built on the premise that EFL readers' metacognitive awareness of reading strategies was also influenced by their multiple intelligence profiles. The purpose of this study is to explore the integrated impact of multiple intelligences and reading strategies on EFL learners' reading performance. This was an explanatory sequential study, combining quantitative and qualitative research design. A convenience sample of 60 high school EFL learners from one of the Anatolian high schools in Istanbul, Turkey participated in this study. Two quantitative surveys and an achievement test, followed by a qualitative observation checklist, were used in this study to collect the data. The results of the study indicated that females were found to be more successful than males in EFL reading in addition to employing more support and problem solving reading strategies. In addition, this study also found that successful readers in EFL seemed to use more global strategies and tended to support reading strategies if they were dominant in musical, intrapersonal intelligences. Moreover, successful musically or verbally intelligent readers were found to use more problem-solving strategies. As a result, this study provides EFL teachers and curriculum designers with valuable information that will foster awareness of the role of these intelligence-strategy relations may play in triggering success in EFL reading, and thus, in their overall proficiency in the language.
Keywords: EFL reading; multiple intelligences; reading strategies; Education & Educational Research